Pendidikan Hak Asasi Manusia dalam Kurikulum "˜Presisi': Studi Sekolah Polisi Negara di Sumatera Utara - Fazli Rachman; Majda El Muhtaj; Reh Bungana Beru Perangin-angin; Prayetno Prayetno (Jurnal HAM, 2024)
This article focuses on the Indonesian Police (Polri) efforts in the realization of human rights-based policing, as well as its articulation in the forming education (pendidikan pembentukan/ DIKTUKBA) of Polri, specifically at the State Police School (Sekolah Polisi Negara/SPN) in North Sumatra, established in 1960-s and one of the oldest SPN in Indonesia. Since 2021, Polri has acknowledged and developed the "˜presisi' curriculum to become a starting point for transformation agenda and, of course, to strive Polri's obligation in the implementation of human rights values, principles and standards in the police functions. The research applied a qualitative approach with a descriptive design. Data collection was employed using documents, FGD, observations and literature relevant to police and human rights issues. Respondents were selected using a purposive sampling technique. Data validation was carried out by extending observations and triangulation and analyzed using the spiral technique. Human rights-based policing through the DIKTUKBA POLRI level at the SPN Poldasu brings the vision of "˜presisi' police through the "˜presisi' curriculum. The "˜presisi' curriculum offers good ways to achieve the transformation of the Polri. However, the increasingly short training period for the DIKTUKBA POLRI represents a challenge to improve human rights-based policing. The challenges affirm the correlation between human rights and policing in a dynamic police workspace. In this context, the instructors's capacity must continuously acquire knowledge and experience. Therefore, collaboration and innovation in using learning models and methods such as group learning, problem-solving, discussion, and active involvement of students can be continuously developed.